Meaningful and inclusive learning as a teaching-learning strategy in graduate programs in technology management and related fields. A proposal for Latin America (Gestión y Gerencia, 2026)
The objective of this work is to propose the application of Roegiers' Integrative Model and Ausubel's Meaningful Learning to the teaching and learning of technology management in Latin American postgraduate programs. The research adopts a qualitative approach, with a documentary-interpretive and argumentative design. Both models are described and contextualized for their application in teaching technology management at the postgraduate level. The results show that integrating these approaches helps students systematically, structurally, and in an organized manner articulate theory with professional and work practice through collaborative networking both inside and outside the classroom. It is concluded that academic training in technology management constitutes a strategic axis for strengthening technological negotiation capacities in Latin American countries and reducing the technological gap and dependence on more developed nations.
Keywords: Meaningful learning; integrative approach; technology management teaching; higher education; technology management